‘IF THEY HINDER TO SPEAK, HOW THEY LEARN IT?’ CAUSE AND SOLUTION FOR STUDENT RELUCTANT TO SPEAK IN SPEAKING CLASS - Bayu Arga Krisna; Ahmad Syafii (STAIN Sultan Abdurrahman Kepulauan Riau, 2020)
This study aims are to find out the factors that make the student hinder to practice their speaking in English classroom. The possible solution to overcome the factors below will be revealed through in-depth interview. The finding of the study of the factors that make student hinder to speak such fear of mistake, shyness, lack of motivation was commonly caused by their personality and also the class environment. The factors shyness was commonly caused by their personalities as a shy person, and the student believe that motivating them to be more confidence in speaking by their teacher is worth considering to make the class environmentbecome more enthusiastic.